PENGARUH SELF-CONCEPT TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DENGAN LINGKUNGAN KELUARGA SEBAGAI VARIABEL MODERASI (Survey Pada Siswa Kelas XI IIS SMA Negeri se-Kabupaten Bandung Wilayah Timur) - Indah Dayanti, - (2021)
The background of this study was learning interest low on economic subjects and the low level of economic involvement the preformance of students learning activities. This study aims to determine the effect of self-concept on learning interest with family environment as moderating variables. The research method used was an explanatory survey using a questionnaire as a data collection tool. The population of this research is IIS XI grade Students of State Senior High Schools in East Bandung Regency. then using a random sample technique obtained as many as 230 student samples. The collected data were then analysed using hierarchical regression analysis techniques and multiplier regression analysis (ARM). The results showed that: (i) learning interest in the high category, self-concept in the medium category, and family environment in the high category; (ii) self-concept has a positive effect on learning interest; (iii) family environment negatively moderates the effect of self-concept on learning interest.